The Dynamics of Agrarian Conflict Governance between PT Lonsum and the Kajang Indigenous Community from the Perspective of Karl Marx's Conflict Theory - Pratama, Eko; Syarifudin, Syarifudin; Firdaus, Firdaus (Kybernology : Journal of Government Studies, 2025)
This research aims to analyze the dynamics of agrarian conflict between PT London Sumatra Indonesia Tbk (PT Lonsum) and the Kajang indigenous community in Bulukumba Regency, South Sulawesi. The conflict arises from overlapping land claims, non-transparent extensions of plantation concessions (Hak Guna Usaha/HGU), and the lack of recognition of indigenous land rights. This study employs a qualitative case study approach using interviews, observations, and document analysis. The findings reveal that the agrarian conflict represents a manifestation of class struggle as described by Karl Marx, where PT Lonsum, as a representation of capital owners, receives state legitimacy to control the land, while the indigenous community faces subordination and marginalization. The Kajang people have carried out various forms of resistance—symbolic, advocative, and collective—including the involvement of youth in protests and legal advocacy. The study concludes that resolving agrarian conflicts requires more than legal-formal approaches; it demands recognition of indigenous land rights, community empowerment, and sustainable social justice